The Use Of Marine Sponge Crude Extract To Improve The Resistance Of Tilapia Fish (Oreochromis niloticus) To Streptococcus agalactiae Infections (Jurnal Ilmiah PLATAX, 2019)
This study aims to examine the effect of the use of crude marine sponge extract on the resistance of streptococcus agalactiae infection in tilapia, Oreochromis niloticus, and to establish the effective dose of crude sponge extract in improving the immune system and the growth of the fish. The sponge used in the study was Cribrochalina sp. taken from Malalayang waters, Manado. The fish were taken from Freshwater Aquaculture Center, Tatelu. The fish were acclimatized for a week. After being acclimatized the fish were given feed added with sponge crude extract as a treatment with different concentrations of 20 g, 40 g and 60 g / Kg of feed for 14 days as much as 5% / body weight / day with the frequency of feeding twice a day at 10:00 am and at 5:00 p.m. After being treated, the fish was challenged with S. agalactiae. The data collected consisted of tilapia resistance, Total Leukocyte Count (TLC) as immune parameters and absolute growth. The results showed that the addition of crude extracts of Cribrochalina sp. into feed can increase TLC and growth of tilapia (p